The effectiveness of using role-play as an educational tool in Teaching tobacco cessation module to dental students - Abllah, Zurainie (2018)
Aims/Background The primary aim of this study was to explore the effectiveness of using role play in teaching Tobacco Cessation Module (TCM) among third-year students in a Dental School in Kuantan, Pahang, Malaysia. Tobacco cessation learning is an important module for dental students to learn. This knowledge then need to be translated in a way as giving a good and effective tobacco cessation session to the patients that they will see as dental professionals. Methodology Third-year students (N=45 students) voluntarily participated in the study were given a set of self-administered questionnaire consisted of demographic questions and questionnaires asking their opinions about role play and the effectiveness in teaching TCM to the dental students. Results Great majority of students (89%) believe that role-play session is both fun and full of pedagogical value in understanding TCM. Most of the students agree (71%) that role-play present many opportunities for learners to show their skills in TCM. The students also believe that lecturers must use role-play for breaking down boredom in teaching (64.4%) and using role-play technique can lower students’ anxiety while learning TCM. Most of the students (78%) also believed that role –play session encourage and teach the fluency in giving TCM advices to patients. Conclusion Role-play session is necessary and helps students to understand better in the purpose of teaching and learning of TCM. The use of role-play as a tool for dental students and other health based students to understand TCM better should be emphasized and improved as it is very beneficial in improving students understanding towards the subject.